(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
CSR orientation refers to Carroll’s (Carroll Shabana 2010) standard CSR programmeorientation process, which is structured in the form of a pyramid and consists of physical, legal, ethical,and charitable requirements. Economic responsibility, the pyramid’s cornerstone, is the organization’skey function as regarded by all stakeholders in society. Judicial responsibility, which extends beyondeconomic duty, guarantees that businesses carry out their legal obligations in accordance with nationallaws and regulations. The company’s planned operations are subject to ethical responsibility, which is atthe top of both legal and economic requirements. The highest level of responsibility, philanthropicaccountability, includes the firm’s behaviour in responding to the ambitions of good corporate citizens ofcommunity. This study includes the CSR orientation because it is crucial in assessing the knowledge ofschool instructors engaging in CSR programmes, and it determines the feasibility of CSR programmes inthe education area.this study tries To gain an understanding of how the Adani group has actedresponsibly toward all of its stakeholders to learn more about the activities, programmes, and strategiesthat the company has established, formulated, and put into action in order to improve educationalopportunities for the general populace.